The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1159/000107097
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and Outcome of Traumatic Brain Injury in an Urban Area in Western Europe over 10 Years

Abstract: Introduction: Valid epidemiological data on incidence and outcome of traumatic brain injury (TBI) show great variability. A study on incidence, severity and outcome of TBI was conducted in an urban area of one million inhabitants. Materials and Methods: 130,000 prehospital emergencies were screened for TBI. Inclusion criteria: Glasgow Coma Scale (GCS) score ≤8 and/or Abbreviated Injury Scale for head injuries (AIShead) score ≧2 with confirmed TBI via appropriate diagnostics. Results: Annual incidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
44
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 116 publications
6
44
1
2
Order By: Relevance
“…Roughly half of the patients had accompanying injuries, and these results are in accordance with other studies [21]. As expected, these injuries were more often observed in high-energy events such as transport accidents [10].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Roughly half of the patients had accompanying injuries, and these results are in accordance with other studies [21]. As expected, these injuries were more often observed in high-energy events such as transport accidents [10].…”
Section: Discussionsupporting
confidence: 90%
“…Severe-TBI fatality rates after admission to hospital are 25–40% [21,22]. In the present study, a fatal outcome was found in 29% of the patients.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…About half of all trauma deaths are said to belong to this group; however, the data vary from 30 to 70% based on various factors, such as type of injury, region, or type of emergency medical system (EMS). Evans et al [5] found that 66% of trauma deaths were prehospital deaths in Australia, Maegele et al [6] found that 61% of patients with traumatic brain injury (TBI) died outside the hospital, and Demetriades et al [7] found a 50% rate for immediate deaths in the county of Los Angeles. However, these very early deaths are usually not seen in hospital-based trauma registries, and the present analysis also could not contribute to this aspect.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, TBI is a highly relevant medical and socio-economic problem of modern society. During the last two decades, improvements in acute pre-and inhospital care, time management, diagnostic procedures, and rehabilitation strategies have substantially improved the level of care and outcome following TBI (Maegele 2007). But still, to date, no therapeutic approach has been proven effective in reversing the pathologic cellular sequelae underlying the progression of cell loss and in improving neurobehavioral outcome.…”
Section: Introductionmentioning
confidence: 99%